2003
DOI: 10.1063/1.1635068
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ga2O3 template thickness and gadolinium mole fraction in GdxGa0.4−xO0.6/Ga2O3 gate dielectric stacks on GaAs

Abstract: Amorphous GdxGa0.4−xO0.6/Ga2O3 gate dielectric stacks have been grown onto the GaAs(001) surface by molecular beam epitaxy using high temperature effusion cells. The Ga2O3 template thickness and the Gd mole percent have been systematically varied from 73 to 0 Å and from 8.8 to 22 at. % (0.088⩽x⩽0.22), respectively. Oxide/n-type GaAs samples have been characterized by high-frequency capacitance–voltage measurements. Optimum gate oxide stack and oxide/GaAs interface properties are obtained with a Ga2O3 template … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Only a few examples include high-electronmobility and heterostructure bipolar transistors, diode lasers, light-emitting diodes, photodetectors, electro-optic modulators, and frequency-mixing components [1][2][3][4]. The operating characteristics of these devices depend critically on the physical properties of the constituent materials, which are often combined in quantum heterostructures containing carriers confined to dimensions * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few examples include high-electronmobility and heterostructure bipolar transistors, diode lasers, light-emitting diodes, photodetectors, electro-optic modulators, and frequency-mixing components [1][2][3][4]. The operating characteristics of these devices depend critically on the physical properties of the constituent materials, which are often combined in quantum heterostructures containing carriers confined to dimensions * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It was suggested as early as 1995 that the low D it property of the oxide-GaAs interface is solely provided by Ga 2 O 3 and that the resistivity of the bulk oxide is related to the depth profile of the Gd concentration. 8,9 Recent studies confirmed the distinctively different roles of Gd mole fraction 10 This letter reports on a systematic study of optical and electrical properties of Gd x Ga 0.4Ϫx O 0.6 films as a function of Gd mole fraction x. These films are part of Gd x Ga 0.4Ϫx O 0.6 /Ga 2 O 3 gate dielectric stacks grown on GaAs͑001͒.…”
mentioning
confidence: 80%
“…5͑b͒, indicates that Fowler-Nordheim ͑FN͒ tunneling is the dominant conduction mechanism. The barrier height was indirectly compared from the negative slope of the linear fitting at higher field, 13 which is accordant with the previous results.…”
mentioning
confidence: 86%
“…The degradation in the film of x = 0.82 is due to charge trapping at the defect site in the oxide. 13 The log͑J / E 2 ͒ vs 1 / E plot in the inset of Fig. 5͑b͒, indicates that Fowler-Nordheim ͑FN͒ tunneling is the dominant conduction mechanism.…”
mentioning
confidence: 93%